ONTOLOGICAL SITUATION OF RUSSIAN EMIGRATION: AN ATTEMPT TO COMPREHEND - Diana E. Kostenko (Вестник Северо-Кавказского федерального университета, 2022)
AN ATTEMPT TO COMPREHEND The article represents attempt of scientific, literary-critical and cultural judgment of destinies of representatives of the Russian intelligentsia which has emigrated after February revolution of 1917. Household and psychological problems of writers of the Russian abroad are considered; their ideological and cultural values, creative crisis and possibility of realization in creativity.